Diagnostico organizacional y propuesta de planeación estratégica para la empresa magro Cía. Ltda. cantón Quevedo, provincia de Los Ríos, año 2013. - Zambrano Toala, Elsa Liliana (2013)
This research wasconducted intheCIAMAQGROcompany. LTDADedicated to the production and marketing ofagriculturalmachinery, agro, carpentry and construction, located in the cantonQuevedofromthe year 2006, itdoes not have astrategicplanthat allows you to: Getsustainable competitive advantagesover competitors; Optimizethe functions of itsemployees not tobe delaysin production;Get betterreturns. The investigations tablished the following objectives: 1)Diagnosethecompany's organizationalsituationMAQGROCIA.LTDA, QuevedoCantonprovince ofLosRíos. 2)Setthe strategic direction ofthe companyMAQGROCIA.LTDA, QuevedoCantonprovince ofLosRíos. 3)Developperformance indicatorsto measurethe achievement of objectives. We developed atheoretical frameworkwherecited severalrenowned authorswho contributed tothe theoretical foundationof the research. By diagnosed results to the company organizationally determined that: • The company does not have a mission and vision to target its activities • The company has a casual organizational • There are defined the objectives, policies and strategies of the business • The resources and capabilities available to the company are insufficient • MAQGRO CIA. LTDA., Has no competence FODA As structuredto enablestrategic planning, project thecompany in the marketto obtaincomparative advantages, sustainable competitiveoptimize theirfunctionsand maintaina profit marginin terms of profitability. The hypothesisis trueaffirmative: "The design of a strategic planfor the companyMAQGROCIA. LTDA.,scenario inwhich toimplementations toachievethe goals set bythe company"